Edukasi Mengenai PHBS, Gizi Pada Ibu Hamil Serta Gizi Pada Lansia Dalam Meningkatkan Kesadaran Kesehatan Pada Masyarakat Desa Belabori, Kabupaten Gowa - Sainah, Sainah Iin; Irmawati, Irmawati; Sofyan, Muhammad; Liliskarlina, Liliskarlina; Nursiah, Nursiah (Patria Artha Journal of Community (PKM), 2023)
Clean and Healthy Lifestyle Education aims to provide a better understanding and provide education related to the Clean and Healthy Lifestyle althy Lifestyle, nutrition for pregnant women and nutrition for the elderly to the community, especially the community in Belabori Village, Gowa Regency. Nutrition education for pregnant women aims to reduce health risks to the fetus and mother. Nutrition education for the elderly aims to increase the number of screenings and form a health intervention strategy through counseling, mentoring and mentoring, increasing the capacity of elderly cadres. The method used in this community service is in the form of theory-based education and practice of a cleanand healthy lifestyle (PHBS) as an effort to prevent and overcome health problems in three stages, namely the preparation stage, the implementation stage, and the evaluation stage. The targets of this community service implementation are the residents of Belabori Village, Gowa Regency. The results of this community service activity are that Belabori Village residents gain knowledge through the stheory and practice-based educational stage on how to apply PHBS (Clean and Healthy Lifestyle), Knowing Nutrition in pregnant women and nutrition in the elderly and applying how to wash hands properly and correctly. Activities carried out during community service are providing education about PHBS, nutrition for pregnant women and conducting leopold examinations for pregnant women and providing education about nutrition for the elderly and conducting tension in the Belabori Village community. From the results of this education, Belabori Village residents can practice a clean and healthy lifestyle such as how to wash hands properly and correctly, delivery assistance is assisted by health workers, babies are given exclusive breastfeeding, weigh babies every month, availability of clean water, eradicate larvae, use latrines. healthy people, not littering and implementing healthy living patterns and behaviors in the community by consuming healthy nutritious food, as well as routinely conducting health checks at the nearest Health Service Center. Keywords: Clean and Healthy Lifestyle, Public Health